Semi-active vibration absorbers for the high-rise objects - Diveyev, Bohdan (Lviv Politechnic Publishing House, 2018)
To determine the optimal parameters of the dynamic vibration absorber (DVA), a complete multi-parameter model of the dynamics of machines and structures is required. A model with two degrees of freedom is unacceptable for a sufficiently precise calculation with sufficient accuracy of the oscillations of the design, and thus for an adequate description of its dynamic characteristics. Therefore, in practice, it is necessary to investigate the design using a complex model. In particular, the methods for determining the concentration of mass and stiffness can be used on the basis of a refined theoretical calculation. A number of numerical schemes (NS) are known for complex vibro-loaded structures, in which developed methods of decomposition and synthesis of NS based on new methods of modal synthesis. Also developed is a complex NS of discrete-continuum type, which provides an opportunity in the adaptive mode to calculate stresses not only in the continuum elements, but also in the places of their greatest concentration - in the compounds. In this paper, an efficient numerical approach based on the theoretical-experimental method is proposed to maximize the minimal damping of modes in a prescribed frequency range for general viscous tuned-mass systems. Methods of decomposition and numerical synthesis are considered on the basis of the adaptive schemes. The influence of dynamic vibration absorbers and basic design elastic and damping properties is under discussion. A technique is developed to give the optimal DVA’s for the elimination of excessive vibration in sinusoidal and impact forced tall buildings system. One task of this work is to analyze parameters identification of the dynamic vibration absorber and the basic structure. The discrete-continue models of machines dynamics of some elongated element with multi mass DVA’s are offered. A technique is developed to give the optimal DVA’s for the elimination of excessive vibration in harmonic stochastic and impact loaded systems. The questions of robustness at optimization of DVA are considered. Different types of control management for semi-active DVA’s are applied. Examples of DVA’s practical implementation are presented.
Keywords: dynamic vibration absorber; semi-active absorber; high-rise object; adaptive scheme; optimization; robustness; design